MODEL CHARACTERISTICS OF HIGH JUMPERS’ COMPETITIVE ACTIVITIES - lona Mihajlović,; Milan Šolaja, (Sport Scientific And Practical Aspects, 2025)
Many scientists studied anthropometric characteristics and kinematic parameters of high jumpers. A number of researches were conducted with the aim to supplement and broaden the existing information. First class track and field achievements are not possible without analysis of adequate biomechanical parameters, which is nowadays the area of scientific study in the field of sport. We made a conclusion based on numerous researches that it is not possible to reach top results without the adequate analysis of the training process. Kinematic parameters of last steps of run-up, take-off and flight, which are velocity, knee angles, angles of hip joint, centre of mass (COM) height and others were obtained through the analysis of various researches data. Based on all the parameters mentioned, this text singles out model characteristics of the competitive activities of best ten high jumpers in the recent years.